Floquet engineering of quantum tunneling in the array of bose-einstein condensates with spin-orbit coupling - Abdul Hadi, Muhammad Salihi (2019)
We demonstrate the existence of compacton matter waves in binary mixtures of Bose-Einstein condensates (BEC) trapped in deep optical lattices (OL) subjected to equal constributions of intra-species Rashba and Dresselhaus spin orbit coupling (SOC) under strong nonlinearity management. The existence of other strongly localized bright soliton and breathers are also presented to show the advantage of the Floquet engineering of quantum tunneling.